Defective ground structure and complimentary split ring resonator loaded compact wideband antenna for radiolocation applications - Nelapati Ananda Rao; Siddaiah P. (Universitas Ahmad Dahlan, 2020)
A wideband compact antenna with wo Bandwidth enhancement techniques intended for radiolocation applications is presented. Defective ground structure (DGS) is used to enhance the bandwidth and complimentary split ring resonator (CSRR) has been used to generate the bandwidth at the lower frequency of the antenna which brings compact nature. A coax feed patch antenna radiating at X-band frequency of 10 GHz is loaded with DGS and CSRR. Proposed antenna with a bandwidth of 3.4 GHz has shown a considerable enhancement in the antenna bandwidth when compared with the antenna with CSRR alone which is having a bandwidth of 1.15 GHz and a basic patch antenna whose bandwidth is 0.91 GHz. Proposed antenna is having omni directional radiation pattern with a gain of 5.01 dB and without any null in the coverage area. A great increase in the current fields can be observed that the field currents by loading the patch and ground with CSRR and DGS respectively. The patch currents have increased from 2.76 v/m to 3.25 v/m and the ground currents have increased from 0v/m to 2.45 v/m. Proposed antenna has been realized and its performance is measured using vector network analyzer, a near match in between the simulated result and measured result is observed.